The modern challenges of regional development and socio-economic potential of town districts belonging to North macro-region of Poland - Iwona Koza (Institute of Economic Research (IER), 2015)
Today, however, the concept of capital strongly focuses on intellectual capital, understood as the current or potential creative resource, or the increase in the wealth of a community. In this context, it is worth to examine the legitimacy of thesis about the expansive reality of Polish town distritcs. Over the past 10 years, in North macro-region, there has been a significant improvement of characteristics relating to intellectual capital. At the same time, gross domestic product per capita in the macro-region annually increased its value. It is, therefore, necessary to maintain and multiply the rate of change in the socio-economic sphere, based on a coherent, harmonious and innovative development strategies, evaluating intellectual potential of the communities.
Keywords: E62; E65; G28; H70; H71; H72; H76; 330; macroregion; town districts; development; socio-economic potential